Persepsi guru-guru sekolah Menengah Daerah Sarikei, Sarawak terhadap latihan dalaman berasaskan sekolah - Abdul Hakim, Bin Mohd Isa. (1998)
This study explored the perception of teachers towards school-based in-house training in 5 secondary schools in Sarikei district, Sarawak. Specifically, the purpose of the study was to examine how school-based staff development could bring about changes in schools in terms of improving the knowledge of teachers involved in the programme, based on the strategies employed, support from school management, teachers' attitude and demographic factors. The sample for the study was This study explored the perception of teachers towards school-based in-house training in 5 secondary schools in Sarikei district, Sarawak. Specifically, the purpose of the study was to examine how school-based staff development could bring about changes in schools in terms of improving the knowledge of teachers involved in the programme, based on the strategies employed, support from school management, teachers' attitude and demographic factors. The sample for the study was a group of 159 teachers from diverse backgrounds.a group of 159 teachers from diverse backgrounds.